CaII‐Catalyzed Alkenylation of Alcohols with Vinylboronic Acids. Issue 31 (1st July 2015) - Lebœuf, David; Presset, Marc; Michelet, Bastien; Bour, Christophe; Bezzenine‐Lafollée, Sophie; Gandon, Vincent
Abstract Direct alkenylation of a variety of alcohols with vinylboronic acids has been accomplished using the air‐stable calcium(II) complex Ca(NTf2)2 under mild conditions with short reaction times. For reluctant transformations, an ammonium salt was used as an additive to circumvent the reactivity issue.